Proceso de atención nutricional en paciente masculino de 50 años con insuficiencia renal y diabetes mellitus. - Bajaña Palma, Nayeli Denis (2022)
The present clinical case is about a 50-year-old patient suffering from chronic renal failure and type II diabetes mellitus who was admitted to the hospital for an emergency presenting a clinical picture characterized by hypoglycemia of 45 mg/dl. The patient underwent an individualized nutritional assessment using anthropometric, biochemical, clinical and dietary indicators. Through the anthropometric indicator, data such as; weight 109 kg, height 1.75 m, waist circumference 115 cm, hip circumference 113 cm, arm circumference 39 cm, BMI 35 kg/m2 (obesity grade II) according to the WHO, in terms of the patient's stage using the formula of Estimated GFR is 15.0 ml/min/ 1.73m² (Stage 4; Severe reduction in GFR). According to the biochemical evaluation, normocytic anemia, bacterial infection, hyperglycemia (glucose 278.3 mg/dL) were observed because the patient suffers from diabetes and kidney damage (uric nitrogen 44 mg/dL; creatinine 4.3 mg/dL). Clinical assessment revealed dehydration and paleness. Regarding the 24-hour reminder, it was observed that the patient has a hypercaloric intake that does not cover the macronutrient needs according to the underlying pathology, a low-salt and low-calorie diet is prescribed, taking into account the patient's conditions, either economically and nutritional, for which it gives a diet of 2000 kcal controlling the consumption of sodium and the type of fat when ingesting.